THE USE OF THE WORDS BARBARISM AND VULGARISM IN THE LANGUAGE OF THE ARTISTIC WORK (American Journal of Research in Humanities and Social Sciences, 2022)
First of all, the level of the process of exchange of ideas is very important in my speaking process. Including ensuring the purity of speech and keeping our language away from units that harm it is a process characteristic of literary language norms, and as a result, purity of speech can be achieved. Being able to speak our mother tongue correctly shows our national values and respect for ourselves and others.